Community Use and Knowledge of Algarrobo (Prosopis pallida) and Implications for Peruvian Dry Forest Conservation - Depenthal, Johanna (2017)
Algarrobo (Prosopis pallida Kunth) is the keystone species in Peru’s highly threatened northern dry forests. Though uniquely adapted to thrive in arid environments, algarrobo extent along the Peruvian coast and particularly in La Libertad region has been drastically reduced by urban growth, agricultural expansion, and wood harvesting. Effective conservation of surviving dry forests in La Libertad will require initiatives grounded in field-based knowledge of surrounding communities’ interactions with algarrobo and their understanding of the trees’ importance. This research investigates how residents of distinct communities in or near the town of San Pedro de Lloc in La Libertad, know, use, and value algarrobo in three nearby dry forests. Methods include interviews with community residents and key stakeholders, as well as observation visits to local forests. Our results indicate that primary current uses of algarrobo include widespread domestic consumption of firewood, charcoal production for commercial use, and dependence on algarrobo dry forests as livestock forage. Community residents also value algarrobo trees for their ecological roles in producing oxygen, preventing the encroachment of sand dunes into neighborhoods, and as cultural patrimony. Building on these findings, we suggest a range of concrete ways in which local knowledge and use of algarrobo can support the conservation of this unique and fast-disappearing forest ecosystem.